Study on Soil Spring Model for Pipe and Silty Clay Interaction Based on Physical Model Test - Liyun Li; Junyan Han; Xiangjian Wang (Advances in Materials Science and Engineering)
The previous soil spring model cannot describe the nonlinear characteristics of soil in elastic stage, and there are some shortcomings in the selection of soil spring parameters in some published codes. Meanwhile, the literatures about the spring model for pipe and silty clay interaction are rare. Thus, a series of pipe-silty clay interaction tests are conducted, and some corresponding experimental results are obtained. The effects of soil properties, pipe diameter, and embedment depth on the horizontal resistance of soil are studied. Based on the experimental results, the failure modes of soil are analysed, and a formula to calculate the peak resistance of soil and the corresponding displacement to peak resistance are proposed. Finally, a method to describe the nonlinear spring stiffness coefficient of silty clay is recommended.